Hypertension in Children: A Comprehensive Review of Contemporary Knowledge and Future Perspectives - Mozer, Maciej; Klasicki, Przemysław; Pietruszka, Wiktoria; Możarowski, Wiktor; Mateńko, Jan Stanisław; Krupa, Agata; Krawczyk, Anna; Potrykus, Maria; Kiełbratowska, Julia; Pałuchowski, Michał (Journal of Education, Health and Sport, 2025)
Introduction: Hypertension is one of the most common, well-documented and potentially reversible risk factors of cardiovascular incidents in the adult population. However, studies are much scarcer when it comes to children. With the obesity epidemic on the rise around the world, clinicians must try and ensure the best possible care is given to the patients in order to avoid potential unfavourable outcomes. Aim of the Study: This study aims to evaluate and summarise current knowledge regarding arterial hypertension in the paediatric population, especially emerging trends, causes, risk factors, and long-term outcomes and outline possible future avenues of research. Materials and Methods: A systemic search of currently available literature was conducted through databases such as PubMed, Google Scholar, ResearchGate, and the Cochrane Library using combinations of keywords such as “paediatric hypertension,” “ treatment,” “screening,” “epidemiology,” and “complications.” The current guidelines by associations around the world, such as the American Academy of Pediatrics (AAP), European Society of Hypertension (ESH) and the Canadian Cardiovascular Society (CCS) were also reviewed. Conclusions: Arterial hypertension has emerged as a condition of growing prevalence within the paediatric population. Research indicates that it is prevalent among individuals with a Body Mass Index (BMI) equal to or exceeding 25. Furthermore, the potential complications associated with this condition are numerous, and prompt diagnosis alongside effective treatment, through lifestyle modifications or pharmacotherapy, is essential to mitigate these risks. Nonetheless, numerous avenues for further research remain available to enhance understanding and treatment strategies of paediatric hypertension.